Controversy over the creation of the Canarian Academy of Language. A glottopolitical analysis - Guerra Casado, Pablo (Boletín de Filología, 2021)
This paper analyzes the controversy over the creation of the Canarian Academy of Language. I adopt a glottopolitical perspective that considers institutional linguistic descriptions as interventions in the public space of language in order to maintain power and organize specific social orders. I examine the antecedents of the study of Atlantic Spanish and Spanish in the Canary Islands from the fifties to the nineties at the Universidad de La Laguna, and I observe a break in the language discourses that construct Canarian Spanish as a symbol of identity, a result of the dynamics of quasi–nationalism in the state of the autonomies. The need for the Canarian Academy of Language functioned as part of the rhetoric of the abandonment of the state and was established in terms of repairing a sociolinguistic trauma that would be solved with the action of philologists.